The Tim-3-Galectin-9 Pathway and Its Regulatory Mechanisms in Human Breast Cancer - Inna M. Yasinska; Svetlana S. Sakhnevych; Ludmila Pavlova; Anette Teo Hansen Selnø; Ana Maria Teuscher Abeleira; Ana Maria Teuscher Abeleira; Ouafa Benlaouer; Isabel Gonçalves Silva; Marianne Mosimann; Marianne Mosimann; Luca Varani; Marco Bardelli; et al. (Frontiers in Immunology, 2019)
Human cancer cells operate a variety of effective molecular and signaling mechanisms which allow them to escape host immune surveillance and thus progress the disease. We have recently reported that the immune receptor Tim-3 and its natural ligand galectin-9 are involved in the immune escape of human acute myeloid leukemia (AML) cells. These cells use the neuronal receptor latrophilin 1 (LPHN1) and its ligand fibronectin leucine rich transmembrane protein 3 (FLRT3, and possibly other ligands) to trigger the pathway. We hypothesized that the Tim-3-galectin-9 pathway may be involved in the immune escape of cancer cells of different origins. We found that studied breast tumors expressed significantly higher levels of both galectin-9 and Tim-3 compared to healthy breast tissues of the same patients and that these proteins were co-localized. Increased levels of LPHN2 and expressions of LPHN3 as well as FLRT3 were also detected in breast tumor cells. Activation of this pathway facilitated the translocation of galectin-9 onto the tumor cell surface, however no secretion of galectin-9 by tumor cells was observed. Surface-based galectin-9 was able to protect breast carcinoma cells against cytotoxic T cell-induced death. Furthermore, we found that cell lines from brain, colorectal, kidney, blood/mast cell, liver, prostate, lung, and skin cancers expressed detectable amounts of both Tim-3 and galectin-9 proteins. The majority of cell lines expressed one of the LPHN isoforms and FLRT3. We conclude that the Tim-3-galectin-9 pathway is operated by a wide range of human cancer cells and is possibly involved in prevention of anti-tumor immunity.